Evaluation of Methylene Blue Sorption onto Low-Cost Biosorbents: Equilibrium, Kinetics, and Thermodynamics - Rekha Singh; Tony S. Singh; John O. Odiyo; James A. Smith; Joshua N. Edokpayi (Journal of Chemistry)
This paper presents a study on batch sorption of methylene blue dye from aqueous solution onto Ginkgo biloba sorbent, a waste material produced during the Fall season in many parts of the world. Batch kinetics, equilibrium, and thermodynamic studies were conducted to evaluate the effect of contact time (0–150 min), sorbent dose (0.5–3.0 g/L), pH (2–11), temperature (30–50°C), initial MB concentration (10–30 mg/L), and particle size (177 μm—590 μm) on the methylene blue dye sorption. More than 99% removal of methylene blue was observed within 120 minutes. A Lagergren pseudo-first-order model, a pseudo-second-order model, and intraparticle diffusion models fitted well to the kinetics experimental data. Langmuir and Freundlich isotherm models also fitted well with the observed equilibrium data. Additionally, removal of methylene blue increased with increase in solution pH. Higher sorption capacity (∼20 mg/g) was observed with smaller particle size (170 μm) as compared to larger particle sizes (590 μm). Thermodynamic parameters such as ∆G°, ∆H°, and ∆S° indicated that the sorption process was feasible, spontaneous, and endothermic in nature. The study shows that Ginkgo biloba leaves have the potential to be an efficient sorbent for the removal of methylene blue from surface water samples.